Accelerating biodiversity descriptions and transforming taxonomic publishing: the first decade of Zootaxa - Zhang, Zhi-Qiang (Zootaxa, 2011)
Zootaxa was launched ten years to help taxonomists overcome the taxonomic impediment by enabling them to describe biodiversity in a rapid and efficient way. The first paper on a new species of flat mite (Acari: Tenuipalpidae) was published in Zootaxa 1 on 28 May 2001 (Moraes & Freire 2001). Unlike many regularly-scheduled journals, each paper in Zootaxa was separately issued and published without delay after acceptance by the editor, and there are no page charges or a small fee to support open access. In addition, Zootaxa offers the flexibility to publish manuscripts of any length, so long as they pass peer review. Many colleagues were excited and encouraged by the prospects of such a brand new journal and some of them joined as associate editors to facilitate rapid processing of manuscripts. The journal has met the needs of authors and sustained an early phase of very rapid growth (Figs 1–3), with issue/paper 1,000 published on 27 May 2005 (Rodiles-Hernández et al. 2005). In the first four years, over 1,100 authors from all over the world published 23,000 pages in Zootaxa (Zhang 2005). Thereafter, short papers of fewer than 60 pages were no longer issued separately because several papers were often published on the same day; instead, short papers were grouped to form standard issues of 60, 64, or 68 pages to save paper, printing and mailing costs, with relatively little effect on the speed of publication.